A frequency determination method for automotive nanosensors - Gurko, A. G.; Sergiyenko, O. Yu.; Гурко, Олександр Геннадійович; Сергієнко, Олег Юрійович (Харківський національний автомобільно-дорожній університет, 2021)
The growing popularity of nanosensors in various automotive applications requires new methods for counting the frequency of electrical signals, into which the measured non-electrical parameters are converted. This need is because automobile nanosensors are to register very small changes in the measured parameters that, besides, can change very fast. The paper proposes for use in automotive nanosensors a frequency calculation method based on the principle of rational approximation, which meets the above requirements.
Метод визначення частоти для автомобільних нанодатчиків
Keywords: automotive nanosensors; frequency measurement; rational approximation; автомобільні нанодатчики; вимірювання частоти; метод раціональної апроксимації; 681.518; 10.30977/BUL.2219-5548.2021.94.0.179